Early Detection and Aggressive Management Is a Key to Success in Management of Childhood Constipation: Aggressive Management of Childhood Constipation - Kalavant, Akshay; A R, Swathy; Shetty, Shrinath; Annigeri, Venkatesh (Iranian Journal of Pediatric Surgery, 2021)
Introduction: Functional constipation is an emerging problem in childhood of Indian subcontinent. If diagnosed early and managed aggressively along with lifestyle modification the success rate of disease treatment improves. Objectives: • To assess whether the pain abdomen is the early feature of constipation • To determine the relationship between good follow ups and the outcome • To determine the minimum duration of laxative therapy in management of constipation Materials and Methods: A retrospective analytical study of 150 children with constipation. Various parameters were considered namely demographic details, eating habits, clinical examination, abdominal radiographs and abdominal ultrasonography. Patients were divided into two groups based on the symptoms at the presentation. The first comparison was between constipation group vs pain abdomen group. Second comparison was between the patients with good follow-ups and bad follow-ups. The finally the duration of laxative therapy was assessed. Data was entered into Microsoft Excel and analysed using SPSS version 25. The categorical variables are presented using frequency and percentages. Chi square tests were used for statistical analysis. p<0.05 is considered as significant value for interpretation of results. Results: All the 150 patients were treated for constipation 70% showed improvement. Eighty percent of pain abdomen group patients also showed improvement in their symptoms suggesting that they might be the subset of larger constipation group. 97.1% patient with good follow-up followed the dietary advice. The study reveals that there is an association between following dietary advice and final improvement. 70.5% who followed dietary advice had good outcome irrespective of the use of regular laxatives. Most of the patients (78 %) showed the improvement with 3- 6 months of laxative therapy. Conclusion: Pain abdomen with stool stasis must be considered as early feature of constipation. Patients with better follow and good dietary habits have significant improvement. Aggressive therapy with two laxatives for 3-6 months can increase the success.